Strategy Guidelines for Enhancing the Competency of Carving Artisans in Thailand - Hongrattanavorakit, Sakarin; Suwannarak, Jomkhwun; Dangsungwal, Nanoln (Journal of Cultural Approach, 2025)
The study aimed to study the strategy guidelines for enhancing the competency of carving artisans in Thailand. Qualitative research gathered data from documents and in-depth interviews with 18 experts. The research instruments were a guided-question interview, SWOT analysis, and the TOWS Matrix to formulate strategies for the competency enhancement of carving artisans in Thailand. The findings revealed that the strengths were that carving artisans possess knowledge, expertise, and techniques in selecting, applying, and utilizing tools, equipment, and materials for carving. In addition, they can create product identities that are accepted and have high returns. In terms of weaknesses, the need for continuous self-training to refine skills and advance pattern development. Additionally, endurance in work and diversification of knowledge in other fields are necessary. For opportunities, governmental and private sector support, educational system improvements, technological advancements aiding learning, and quality enhancement of raw materials. The challenges are the absence of standardized professional criteria for carving artisans set by governmental bodies, which hindered competency assessment and altered external perceptions of the profession. The strategy guidelines for enhancing the competency of carving artisans in Thailand encompassed proactive measures such as competition management at various levels, establishing recognition, utilizing artificial intelligence (AI) for pattern design, and knowledge transfer from experienced artisans to new generations. Corrective actions involved promoting appreciation for carving, proposing carving as a conservation profession to the government, organizing carving training, and compiling technical knowledge to disseminate to interested individuals. Preventive strategies included establishing supportive workplaces, addressing labor market demands, pushing for professional standards creation, and developing locally produced carving tools and equipment. Additionally, facilitating access to copyrighted pattern information aims to prevent copyright infringement. Lastly, reactive strategies involve aligning course content with professional standards, offering specialized training courses, and fostering the competency development of carving artisans.